The effect of nitrogen and temperature changes on Solidago canadensis phenotypic plasticity and fitness. Issue 4 (24th June 2020) - Ren, Guang‐Qian; Yang, Hong‐Yu; Li, Jian; Prabakaran, K.; Dai, Zhi‐Cong; Wang, Xiu‐Pu; Jiang, Kun; Zou, Chris B; Du, Dao‐Lin
Abstract: Phenotypic plasticity is commonly considered to contribute to the invasion success of invasive species. However, the importance of phenotypic plasticity, nitrogen (N) levels and warming to the invasion of invasive species is unclear. The effects of warming and N addition on the morphology, biomass allocation and biochemistry traits of Solidago canadensis and their plasticity were investigated by conducting a pot experiment. The results showed that the effect of N addition on biomass was improved for S. canadensis ; whereas warming displayed no significant effect, their positive synergistic interact effect resulted in the overall significant increase in plant performance. The mean phenotypic plasticity indices (MPPI) of biochemistry and total parameters demonstrated a difference between operations, and the higher value was observed in N interaction with temperature treatments than N addition or warming alone. The observed MPPI indicated the biochemistry parameters > morphological parameters > allocation parameters. The MPPI of biochemistry parameters, morphological parameters and total parameters exhibited significant and positive correlations with N level and MPPI of morphological parameters was also significantly positively correlated with the fitness of S. canadensis . These results indicated that the global warming and N addition would make the invaded habitat more suitable for the growth of invasive S. canadensis, and even may effectively increase the invasion risk of S. canadensis through the enhanced phenotypic plasticity, which is a crucial factor to help species deal with the changing environment. Abstract : The effect of N addition on biomass was improved for Solidago canadensis ; whereas warming displayed no significant effect, their positive synergistic interact effect resulted in the overall significant increase in plant performance. The mean phenotypic plasticity indices (MPPI) of biochemistry and total parameters demonstrated the higher values were observed in N interaction with temperature treatments than N addition or warming alone. The MPPI of biochemistry parameters, morphological parameters and total parameters exhibited significant and positive correlations with N level and MPPI of morphological parameters was also significantly positively correlated with the fitness of S. canadensis .